For the History of Ritualistic Practices in the Caucasus - Sikharulidze, Ketevan ("Intercultural Dialogues" Transactions, 2025)
This article examines several calendar customs practiced by the peoples of the Caucasus, particularly those involving door-to-door processions. Folkloric and ethnographic observations reveal that such customs across the region share similar structures and content. Notably, the participants in these processions consistently requested food rather than other gifts — a detail that points to the rituals’ connection with fertility cults. One of the earliest and most prominent of these rituals is khnuli, typically held in spring and involving the entire village. The process featured spell-like chants intended to bring about desired outcomes. Among the most elaborate spring festivals was Berikaoba, a multi-day celebration with numerous episodes designed to invoke the rebirth of nature and promote agrarian prosperity. Characterized by its dramatic elements, Berikaoba is closely associated with the fertility cult. Over time, the door-to-door rituals incorporated improvisational performances, masks, and other theatrical devices. Participants often wore goat or sheepskin garments, likely remnants of older ritualistic symbolism tied to invasion motifs. Across the Caucasus, leather garments were symbolically linked to fertility deities — a connection supported by archaeological discoveries, wall paintings, and depictions of sheep and goats in material culture. Both in Georgia and the North Caucasus, these door-to-door customs were documented and studied during the 19th and 20th centuries, at which point they had acquired an entertaining and often comic character. Yet, even in their grotesque forms, they retained traces of ancient fertility rites. The shared structure and symbolic elements of these rituals underscore the common worldview and cultural unity of the Caucasian people